Bangladesh : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2003)
This report addresses Bangladesh's Interim Poverty Reduction Strategy Paper. For implementing the strategy, a medium-term macroeconomic framework has been specified covering FY04 and FY06. Bangladesh witnessed significant success in disaster preparedness and in overcoming the phenomena of mass starvation and the threat of famine syndrome in the backdrop of endemic vulnerability to natural disasters. The government acknowledges the need for pre-disaster mitigation and preparedness of the people as opposed to the earlier concepts of responding after a disaster has taken place as a necessary as well as a cost-effective approach.